Immunotherapy-based regimens for patients with EGFR-mutated non-small cell lung cancer who progressed on EGFR-TKI therapy - Ying Wu; Yan Ling; Bao-Dong Qin; Xiao-Dong Jiao; Ling-Yan Yuan; Yuan-Sheng Zang (Journal for ImmunoTherapy of Cancer)
The sustained benefit of immunotherapy-based regimens in epidermal growth factor receptor (EGFR)-mutated non-small cell lung cancer (NSCLC) after EGFR-tyrosine kinase inhibitor (TKI) failure is debatable. Neither Checkmate-722 nor Keynote-789 reached the prespecified statistical level of clinical benefit, but the ORIENT-31 and ATTLAS trials showed that the addition of a VEGF inhibitor to immunotherapy plus chemotherapy could significantly prolong survival. However, head-to-head comparisons of the efficacy of immunotherapy plus bevacizumab with chemotherapy versus that of immunotherapy with chemotherapy in this patient population are lacking. In addition, the critical question of who would benefit from an immunotherapy-based regimen remains unclear. We conducted an indirect comparative meta-analysis using chemotherapy as a common comparator to classify the relative efficacy of the two immunotherapy-based regimens. The indirect comparison showed that immunotherapy and bevacizumab plus chemotherapy had a significantly better progression-free survival (PFS) (HRIO+Bev+Chemo/IO+Chemo=0.71, 95% CI 0.55 to 0.91) than immunotherapy plus chemotherapy. The EGFR mutation type and T790M mutation were found to be significantly associated with PFS of immunotherapy-based regimens. Compared with their counterparts, patients with L858R (HR 0.52, 95%CI 0.37 to 0.72), without T790M mutation (HR 0.50, 95% CI 0.35 to 0.71) tended to benefit significantly more from immunotherapy-based regimens. In conclusion, our findings support that the addition of VEGF inhibitor to immunotherapy and chemotherapy could be the preferred option for TKI-resistant, EGFR-mutated NSCLC, and that L858R mutation and T790M negativity could be identified as efficacy-associated factors for immunotherapy-based regimens.